Elementary Logic - For Software Development - Lover, Robert (Springer, 2017)
The ability to reason correctly is critical to most aspects of computer science and to software development in particular. This book teaches readers how to better reason about software development, to communicate reasoning, to distinguish between good and bad reasoning, and to read professional literature that presumes knowledge of elementary logic. It explains fundamental concepts and provides reader-friendly instructions for applying logic to software development